2021
DOI: 10.1186/s13018-021-02696-9
|View full text |Cite
|
Sign up to set email alerts
|

Complex ruptures of the quadriceps tendon: a systematic review of surgical procedures and outcomes

Abstract: Background Chronic ruptures, ruptures following total knee arthroplasty (TKA), and re-ruptures of the quadriceps tendon (QT) are rare. A systematic review of the current literature was conducted on their treatment and outcome to provide evidence-based indications for their management. Methods We searched published articles in English on chronic ruptures of QT, QT ruptures that occurred after TKA, and re-ruptures in PubMed, Scopus, and Google Schola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 45 publications
0
16
0
2
Order By: Relevance
“…Interestingly, the re-rupture rate was found to be 11% in the study population compared to studies including younger patients with reported re-rupture rates of 2% [ 2 ]. Oliva et al also described 9% re-ruptures in a systematic review on complex QTR [ 14 ]. This finding may emphasize the need to identify previously described risk factors which can be addressed during surgery such as osteophytes near the patella pole or pre-existing tendinosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, the re-rupture rate was found to be 11% in the study population compared to studies including younger patients with reported re-rupture rates of 2% [ 2 ]. Oliva et al also described 9% re-ruptures in a systematic review on complex QTR [ 14 ]. This finding may emphasize the need to identify previously described risk factors which can be addressed during surgery such as osteophytes near the patella pole or pre-existing tendinosis.…”
Section: Discussionmentioning
confidence: 99%
“…Advanced age and obesity have already been associated in the literature with an increased risk of rupture due to fatty degenerative changes, loss of collagen and tendon calcification [ 8 ]. In these conditions, MRI can provide additional information about tendon quality and muscular atrophy [ 14 ]. This detailed information can be helpful for surgeons to choose the best possible strategies for tendon debridement and refixation in an older and overweight population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While goniometers were utilized to establish the study's baseline of 5" EL, the examiner relied solely on visual inspection to establish the participant's actual range of motion during trial assessments. It is important for the examiner to be at the same eye level as the patient's lower extremity in order to properly evaluate any movements in the sagittal plane (Oliva F, 2021). A total of 194 measurements of tibiofemoral, patellofemoral, and superior tibiofibular articular pain, stiffness, and crepitus were taken.…”
Section: Discussionmentioning
confidence: 99%
“…The inability to achieve full range of motion in a joint is a hallmark symptom of muscle laziness. Strive for passive limits that require minimal effort and can be achieved despite the resistance of joint stiffness or other soft tissue tightness (Oliva F, 2021).…”
Section: Introductionmentioning
confidence: 99%